Floral diversity and conservation status of vascular plants in arid mountainous areas - Sara Hassanen; Elsayeda Gamal Eldin; Wafaa Kamel; Mohamed Saad Zaghloul; Yasmin M. Hassan (BMC Ecology and Evolution)
Abstract Background The destructive human activities, encroachment of natural habitats, and hyperarid climate threaten the wild flora of the unprotected mountainous areas facing the Gulf of Suez, Egypt. So, this study aims to revise and give an updated systematic status of the flowering plants growing there to conserve and utilize valuable biodiversity. Results This study showed the presence of 136 species, including 7 sub-species of vascular plants, 12 species of monocots, and 124 species dicots belonged to 98 genera and 37 families. The most species-rich families were Asteraceae (22 species) and Amaranthaceae (19 species). Therophytes and Chamaephytes were the most dominant life- forms in the study area, representing 38.2%. They were followed by Phanerophytes, Hemicryptophytes, and Cryptophytes, which represented 11%, 8.8%, and 2.9%, respectively. Five plant assemblages were identified by TWINSAPN classification namely, Zygophyllum coccineum –Haloxylon salicornicum assemblage, Zilla spinosa -Zygophyllum coccineum assemblage, Zygophyllum coccineum-Tamarix nilotica assemblage, Tamarix nilotica – Phargmites australis assemblage and Tamarix nilotica–Chenopodium murale assemblage. Several invasive species were recorded in some wadis. However, their presence is unusual to the floristic composition of the wadis in general and acts as an alarm to protect the native species from anthropogenic interference. Moisture content, organic matter, electrical conductivity, pH, cations, anions, and total carbonate were identified as the significant factors controlling distribution of plant clusters by detrended correspondence analysis. This study recorded Tribulus mollis as a new addition to Egypt’s flora of Eastern desert. Conclusion The comparative analysis of the present and past floral studies in the study area reveals a significant change in the plant community composition. This shift is likely attributed to the adverse impacts of climate change and anthropogenic activities. Thus, this area has to be safeguarded with practical strategies that aid in preserving the significant uncommon flora.